Moral Education from the Perspective of Hadith in Shaping a Pious Generation - Asril Azhari Hasibuan; M. Hasan Ishfi; Muhammad Zakir Hasibuan; Afdhalurrahman; Zulfahmi Lubis (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine and analyze moral education from the perspective of hadith as a foundation for shaping a pious generation. Using a qualitative approach and the Maudu'i method, the research investigates hadiths related to moral education and their relevance in the context of modern education. The findings reveal two primary hadiths analyzed in depth concerning moral education: first, the hadith about proximity to the Prophet Muhammad (peace be upon him) on the Day of Judgment for those with noble character (narrated by At-Tirmidhi); and second, the hadith stating that the most perfect believer is the one with the best character (narrated by Abu Dawud). The analysis of the isnad (chain of transmission) and matn (content) of these two hadiths indicates a hasan-sahih quality, reinforcing their validity as a basis for moral education. This research also highlights that hadith-based moral education has strong relevance in shaping a pious generation in the modern era, particularly in addressing the challenges of moral degradation and the negative impacts of globalization. The implementation of moral values taught in these hadiths can serve as an effective solution for cultivating a young generation that is not only intellectually capable but also possesses high moral integrity and piety.